Relationship between short-term self-reported dietary magnesium intake and whole blood ionized magnesium (iMg2+) or serum magnesium (s-Mg) concentrations - Velarie Y. Ansu Baidoo; Krisha Thiagarajah; Carmen D. Tekwe; Taylor C. Wallace; Nana Gletsu-Miller (Annals of Medicine, 2023)
AbstractObjective Since we and others have shown that supplemental magnesium raises whole blood ionized magnesium (iMg2+) we investigated the relationships between self-reported dietary magnesium intake and concentrations of whole blood iMg2+ and serum magnesium (s-Mg).Methods We obtained whole blood iMg2+ concentrations, as well as s-Mg concentrations, from a pilot, three-arm, randomized, controlled, crossover bioavailability study of magnesium supplements (n = 23; 105 measures). Dietary magnesium intake was assessed using three-day food records and the Nutrition Data System for Research (NDSR, University of Minnesota, MN, USA). Whole blood iMg2+ was measured with an electrode analyser (NOVA Biochemical, Waltham, MA, USA), whereas s-Mg was measured using atomic absorption spectroscopy. A linear mixed-effects model was employed with dietary magnesium as the outcome variable and iMg2+, s-Mg, study treatment and study visit as fixed effects. We adjusted age, gender, race and body mass index covariates.Results Values for dietary magnesium, iMg2+ and s-Mg were 303.8 ± 118.9 mg/day, 1.3 ± 0.1 mg/dL and 2.2 ± 4.1 mg/dL, respectively. No association was found between dietary magnesium intake and iMg2+ −125 ± 176.95 (p = .49) or s-Mg −9.33 ± 5.04 (p = .08).Conclusions Whole blood iMg2+ and s-Mg concentrations do not reflect short-term self-reported dietary intake in adults. Further research is needed to determine whether blood biomarkers of magnesium may reflect dietary magnesium intake.Key messagesDietary intake of magnesium, a shortfall nutrient, may be objectively measured using blood biomarkers of magnesium.Serum magnesium and whole blood iMg2+ were not associated with short-term dietary intake of magnesium.